PRINSIP KESANTUNAN BAHASA DALAM KOLOM KOMENTAR INSTAGRAM @NIKITAMIRZANIMAWARDI_172 - Ayu Apriliya; Mardiningsih; Sugianti (JBI : Jurnal Bahasa Indonesia, 2024)
Communication in social media is one form of someone's concern for others, but it can also be hateCommunication in social media is one form of someone's concern for others,but it can also be hate speech among them. In this study, the researcherwill explain the form of analysis of compliance and deviation of the principle of politeness of language on Instagram social media. This study was conducted to analyze and describe the form of compliance and deviation and violations that occur in the principle of politeness of language in the comment column of Instagram @nikitamirzanimawardi_172. The purpose of conducting research withthis approach is to collect information in more depth and real. This method is considered by the researcher to be very suitable forhis research which indeed aims to describe and analyze compliance with the principle and deviation of the principle of politeness of language in the comment column of the Instagram account @nikitamirzanimawardi_172. So in this case, the researcher will record the speech in the Instagram column on the account with posting deadlines between January 2, 9, 11, 16 and 26 2024. Researchers found 32 sentences of speech that showed compliance with the principles of linguistic politeness. The factors that cause compliance with the principles of politeness include intonation, the speaker's emotions and the choice of appropriate words and sentences. Apart from that, researchers also found 16 forms of speech that showed deviations from the principles of language politeness. Keywords : Compliance; Deviation; Principles of linguistic politeness; Instagram social media comments